Neurobiological and behavioural responses of cleaning mutualisms to ocean warming and acidification - Paula, José Ricardo (2019)
This study was funded by Portuguese national funds through FCT - Fundacao para a Ciencia e Tecnologia, I.P., within the project MUTUALCHANGE - PTDC/MAR-EST/5880/2014, ASCEND - PTDC/BIA-BMA/28609/2017. FCT also supported this study through a PhD scholarship to JRP (SFRH/BD/111153/2015), Programa Investigador FCT to RR (IF/01373/2013). The Swedish Research Council (VR) supported SW. This study was co-funded by Programa Operacional Regional de Lisboa, Portugal 2020 and the European Union within the project LISBOA01-0145-FEDER-028609.